Rethinking the Stage in the 1920s: the Influence of the Bauhaus and International Theatrical Avant- garde in Croatia and Slovenia - Magaš Bilandžić, Lovorka (Array, 2014)
Sažetak: The first decades of the 20th century were marked by significant changes in all areas of artistic development and a search for new means of expression. Theatre has assumed a new importance for avant-garde artists and became a kind of laboratory and testing ground for theories and innovative concepts of Russian Constructivists, Italian Futurists, Bauhaus artists and many others. The search for a new type of theatre included experiments with mechanic, plastic and marionette theatre, moving scenery and kinetic stage as well as redefinition of the play and performance. In realized and imagined projects of Bauhaus artists and other key protagonists of international avant-garde, actors were transformed into robotic, puppet-like figures and dancing automatons suggesting depersonalized and mechanized humanity or disappeared in theatrical performances reduced to the interplay of forms, colours and lights on the stage. The lecture will focus on the Bauhaus Bühnenwerkstatt and the experiments of Oskar Schlemmer, Kurt Schmidt, Andor Weininger and others, its place in the international theatrical avant-garde of the 1920s and transfer of influences to the Central European context. Special emphasis will be put on theatrical experiments and rethinking of the stage in the work of Bauhaus student Avgust Černigoj and Croatian artist Sergije Glumac. Their search for the "new theatre" and non-illusionistic stage surpasses the local scene − it is a part of the key avant-garde currents which marked the 1920s and redefined the perception of performing arts of the period.